Uma análise das normas antecedentes e reservas de alternativas mobilizadas na atividade de motoristas e entregadores por aplicativos - Denise Alvarez; Letícia Pessoa Masson; Simone Santos Oliveira; Cirlene de Souza Christo; Samara Leal; Gabriela Siqueira Salomão; Sarah de Paulo do Amaral (Laboreal, 2021)
This article analyzes, in a situated perspective, the antecedent norms that affect the work of platform drivers and food delivery couriers who work using on-demand apps, in order to discuss the implications of these current forms of control and algorithmic management of work. It also seeks to identify elements of collective action that refer to the mobilization and construction of reserves of alternatives. From the ergological perspective, the research method was based on Meetings about the Work, preceded by documentary analysis, questionnaires, and interviews. The results point to demands and challenges imposed by this management method, as well as to the renormatizations carried out in the construction of reserves of alternatives, and, among them, the establishment of sociability networks. It also discusses how the absence of state regulation, as well as the sophisticated and complex technology incorporated by the platform companies can contribute to deepening the process of social insecurity and exploitation of workers.